Age and sex influence on bone and blood lead concentrations in a cohort of the general population living in Toronto. (3rd February 2017) - Behinaein, S; Chettle, D R; Fisher, M; Manton, W I; Marro, L; Fleming, D E B; Healey, N; Inskip, M; Arbuckle, T E; McNeill, F E
Abstract: Objective : To study the age and sex influence on bone and blood lead concentrations in a cohort of the general population living in Toronto. Approach : A 109 Cd K x-ray fluorescence (KXRF) measurement system was used from 2009 to 2011 in a study that measured the bone lead (Pb) concentration of 263 environmentally exposed individuals residing in Toronto, Ontario, Canada. Tibia (cortical bone) and calcaneus (trabecular bone) lead contents were measured in 134 males and 129 females between 1 and 82 years of age. Whole blood Pb concentration was measured by TIMS (thermal ionization mass spectrometer). Tibia (Ti) and calcaneus (Cal) Pb were examined versus the age of participants, taking into account uncertainties in bone Pb measurement values. Main results : No significant sex differences were observed in any of the age categories. Participants older than 50 years of age demonstrated the highest concentrations of Pb in their blood, tibia, and calcaneus bones. Significance : In most of the previous publications, uncertainty was not considered in the regression model of bone Pb and age. However, in this paper, we adjusted the bone Pb values for the uncertainty level. This had a significant influence in regression models of bone Pb and thus we recommend that uncertainty be considered in future studies.